Ecological intensification with cover crops : relationship between mycorrhizal fungi and maize crop yield in the Argentine Pampas region - García-Parisi, Pablo; Restovich, Silvina Beatriz; Omacini, Marina; Copia, Pablo Antonio; Farroni, Abel Eduardo; Azich, Pablo (Sociedad de Biología de Chile, 2023)
Poster